Coconut layer cake murder ebook - Fluke, Joanne (Hannah Swensen Mystery, 2020)
New York Times Bestseller USA Today Bestseller Publishers Weekly Bestseller Bakery owner Hannah Swensen is leaving Lake Eden to help a friend in sunny California. But an unexpected phone call swiftly brings her back to a cold Minnesota winter . . . and murder . . . When Hannah learns that her sister Michelle's boyfriend, Detective Lonnie Murphy, is the prime suspect in a murder case, she flies straight home from a Los Angeles movie sound stage to frigid Minnesota. But proving Lonnie's innocence will be harder than figuring out what went wrong with a recipe, especially with Lonnie's hazy memory of the night in question. Hannah doesn't know what to believe. Before everything comes crashing down on Lonnie like a heaping slice of coconut layer cake, it'll be up to Hannah to rack up enough clues to toast a flaky killer . . . Features Over a Dozen Cookie and Dessert Recipes from The Cookie Jar!